Disposal of the large volume of sputum positive for Mycobacterium tuberculosis by using microwave sterilisation technology as an alternative to traditional autoclaving in a tertiary respiratory care hospital in Delhi, India - Vithal Prasad Myneedu; Amit Aggarwal (Elsevier, 2020)
Summary: Background: Everyday, tuberculosis hospitals collect enormous amount of sputum containing viable Mycobacterium tuberculosis bacilli, the disposal of which is a challenging task. Chemical (5% phenol) and physical (autoclaving) disinfection methods involve cost, space and cause further environmental degradation. Over the years, use of microwave for sterilisation of biomedical waste has become widespread. However, its efficacy to sterilise large volume of M. tuberculosis positive sputum has never been investigated. Aim: To evaluate the effectiveness of microwave in sterilising large volumes of M. tuberculosis positive sputum samples. Methods: 226 sputum samples positive for M. tuberculosis were checked by Ziehl-Neelsen staining and liquid culture (MGIT ™) both before and after microwaving. χ2 test was performed, and p-value <0.05 was considered significant. Findings: Before microwaving, samples containing acid fast bacilli (AFB) and live M. tuberculosis bacilli were 93.8% and 95% (≈94.7%) respectively; which came down to 14.2% (32) and <1% (≈0.9%) in post microwave. In the 32 post-microwave AFB positive samples, bacilli appeared apoptotic, decreased in size, fragmented, loosely arranged and were easily missed as stain artefacts. Their beaded appearance was not appreciable. Background pus cells were of smaller size, did not take up methylene blue stain properly, and multilobed nuclear material was missing. Conclusion: The study shows efficacy of microwave as an alternative sterilisation method for large volume sputum samples containing M. tuberculosis bacilli. Microwave can become an effective sterilisation method, especially for isolated tuberculosis care centres in countries which struggle for disposal of sputum, the biomedical waste.